TOURISM COMMUNICATION IN INDONESIA SOCIAL MEDIA - Nela Widiastuti (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Melaka is known to have historical values, even the beginning of the birth of Malaysia began in this country. Melaka is also known as the main maritime trade center in this region precisely in the 16th century. Traders from various countries such as Arab, China, India and Europe also came to Malacca to trade silk, spices, gold and porcelain. Therefore on July 7, 2008 UNECSO recognized Melaka as a World Heritage City State together with Georgetown, the State of Penang. Now, Melaka is here to offer a variety of tourism products based on 13 Tourism Product Sub-Sectors, including History, Culture, Recreation, Sports, Shopping, Conventions, Health, Education, Agro Tourism, Culinary, Melaka My Second House, Youth Tourism and Ecotourism. With the theme